Análise de viabilidade econômica e ambiental para a implantação de sistema de geração de energia renovável em uma residência unifamiliar - Souza, Luciano Gonçalves de (Universidade Federal de São Carlos, 2021)
The demand for energy has been increasing since the industrial revolution, mainly of oil and coal, resulting in the exhaustion of its deposits and the pollution of the environment. Due to the environmental liabilities generated by these forms of energy and the scarcity of these natural resources, the need for replacing these energy matrices arose, giving space for the use of renewable energy. This is a case study of economic and environmental feasibility for the implementation of photovoltaic system in a single-family residence. From an economic point of view, in a period of 25 years, there is an estimated reduction in electricity expenditure of 85.2%, and this applies to monthly consumption as well, the system has a useful life of 25 years and the cost of installing the equipment is paid in a relatively short time; in the case of this study, the return time was 4 years, but it varies between 4 and 6 years. In the analysis of environmental viability, the negative ecological balance was obtained as a result, making the photovoltaic system for the analyzed residence ecologically unsustainable, because residents consume resources above the biocapacity of the planet from nature.
Economic and environmental feasibility analysis for the implementation of renewable energy generation system in a single family home
Keywords: Fontes renováveis de energia; Energia fotovoltaica; Residência unifamiliar; Viabilidade; Renewable energy sources; Photovoltaics; Single-family residence; Viability; ENGENHARIAS